A (C)osmosis Art in-Between Disciplines. - Michaloudis, Ioannis (Cambridge Scholars Publisher, 2021)
The relationship of humankind to the cosmos has a very long history, and has raised many more questions than can be adequately answered. Why has the cosmos been a source of awe and wonder since the beginning of civilizations? How are the arts of today related to our engagement with the cosmos? Who are the contemporary practitioners working in this field? This volume is the first publication on this particular theme written for a general audience, and initiates a discourse on art inspired and driven by the fact that humans are enthusiastic observers of Earth and the universe surrounding it. Fur.